Households' responses to spousal job loss: 'all change' or 'carry on as usual'? - Karon Gush; James Scott; Heather Laurie (University of Essex, Institute for Social and Economic Research (ISER), 2013)
Economic theory suggests that when a primary earner within a couple loses their job, one potential response is for the secondary earner to seek additional paid work to bolster their household finances. Yet, the empirical quantitative evidence regarding any such 'added worker effect' is mixed. To investigate why this might be, we explore the processes behind household responses to job loss through qualitative interviewing techniques. The findings indicate that the use of additional spousal labour is only one response of many alternatives and typically only invoked in cases of serious financial hardship.
Keywords: D13; J22; J64; 330; Couple-households; labour supply; recession; job loss; qualitative interviews; Understanding Society Innovation Panel